2007
DOI: 10.1111/j.1365-2044.2007.05071.x
|View full text |Cite
|
Sign up to set email alerts
|

Combined coronary artery bypass grafting and phaeochromocytoma excision

Abstract: SummaryWe report two patients who had successful combined coronary artery bypass grafting and excision of phaeochromocytoma. These cases represent the first reports of combined coronary artery bypass grafting and laparoscopic adrenalectomy for phaeochromocytoma and of combined coronary artery bypass grafting and excision of extra-adrenal phaeochromocytoma. With careful peri-and intra-operative management, especially in regard to haemostasis, combined operations for coronary artery disease and phaeochromocytoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
(45 reference statements)
0
5
0
Order By: Relevance
“…The risk of perioperative mortality during a pheochromocytoma operation can be reduced from 45% to approximately 3% with the judicious use of these treatments . The presence of severe coronary artery disease makes adrenergic blockade even more imperative since even small fluctuations in blood pressure can adversely shift the myocardial supply‐demand balance and cause ischemia . Intraoperatively, the anesthesiologist must be prepared to manage a hypertensive crisis using phentolamine, a short‐acting alpha antagonist.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk of perioperative mortality during a pheochromocytoma operation can be reduced from 45% to approximately 3% with the judicious use of these treatments . The presence of severe coronary artery disease makes adrenergic blockade even more imperative since even small fluctuations in blood pressure can adversely shift the myocardial supply‐demand balance and cause ischemia . Intraoperatively, the anesthesiologist must be prepared to manage a hypertensive crisis using phentolamine, a short‐acting alpha antagonist.…”
Section: Discussionmentioning
confidence: 99%
“…A few cases in the literature have described the hemodynamic challenges of performing CABG in a patient undergoing pheochromocytoma resection concurrently . To our knowledge, however, no reports exist of a patient surviving surgical coronary revascularization with metastatic pheochromocytoma.…”
Section: Discussionmentioning
confidence: 99%
“…Successful CABG both on and off-pump, 3 mitral valve replacement, 4 concurrent CABG with adrenalectomy, 5 and even heart transplant 6 have been described in patients with pheochromocytomas. We described a patient with an unanticipated pheochromocytoma undergoing combined AVR-CABG and postulate that the favorable outcome despite the hypertensive crisis was a result of (1) a high index of suspicion; (2) immediate aggressive treatment of the hypertension bearing in mind its pathophysiology, using phentolamine and labetalol; (3) expeditious surgery with short duration of aortic cross-clamping; and perhaps, (4) the quick implant time of a new sutureless prosthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Presence of a concomitant phaeochromocytoma in a patient with coronary artery disease requires careful preoperative and intraoperative management of both pathologies in terms of blood pressure control, myocardial protection and haemostasis. To et al reported the first successful cases of combined coronary artery bypass grafting and laparoscopic adrenalectomy for phaeochromocytoma and excision of extra adrenal phaeochromocytoma [ 28 ]. Subsequent successes were described by Garg et al [ 29 ] and Balabaud-Pichon et al [ 30 ].…”
Section: Discussionmentioning
confidence: 99%